Potential Use of Beneficial Microorganisms for Soil Amelioration, Phytopathogen Biocontrol, and Sustainable Crop Production in Smallholder Agroecosystems - Koskey, Gilbert; Mburu, Simon Wambui; Awino, Richard; Njeru, Ezekiel Mugendi; Maingi, John M. (Frontiers in Sustainable Food Systems, 2021)
Smallholder agroecosystems play a key role in the world's food security providing more than 50% of the food produced globally. These unique agroecosystems face a myriad of challenges and remain largely unsupported, yet they are thought to be a critical resource for feeding the projected increasing human population in the coming years. The new challenge to increase food production through agricultural intensification in shrinking per capita arable lands, dwindling world economies, and unpredictable climate change, has led to over-dependence on agrochemical inputs that are often costly and hazardous to both human and animal health and the environment. To ensure healthy crop production approaches, the search for alternative ecofriendly strategies that best fit to the smallholder systems have been proposed. The most common and widely accepted solution that has gained a lot of interest among researchers and smallholder farmers is the use of biological agents; mainly plant growth promoting microorganisms (PGPMs) that provide essential agroecosystem services within a holistic vision of enhancing farm productivity and environmental protection. PGPMs play critical roles in agroecological cycles fundamental for soil nutrient amelioration, crop nutrient improvement, plant tolerance to biotic and abiotic stresses, biocontrol of pests and diseases, and water uptake. This review explores different research strategies involving the use of beneficial microorganisms, within the unique context of smallholder agroecosystems, to promote sustainable maintenance of plant and soil health and enhance agroecosystem resilience against unpredictable climatic perturbations.